KEEPING SELOKO POETRY AND POEM OF TRADITION ADAT JAMBI DIGITALLY SAFE: THE UNSWERVING OF ISSUES, OBSTACLES, AND GAPS - Riady, Yasir; Riady, Hamdi (Universitas Gunadarma, 2023)
The government of Jambi Province wanted to preserve the Malay culture as part of the province's identity. One of the traditions is Seloko. Jambi Province is one of several provinces in Indonesia that share the same cultural history as the Malay with its original culture. Jambi Malay traditional Seloko are expressions that use proverbs, phrases, pantun, and figurative language to convey messages, suggestions, morals, and other important information. This article's goal is to describe the Seloko Adat Tradition's digital preservation in Jambi, which is currently difficult to do. It does so by outlining the difficulties, knowledge gaps, and problems involved. The investigation was conducted using a descriptive analytical analysis coupled with observations of the current digital preservation support. The digital preservation in this article provides a snapshot of the work that the government, academics, librarians, locals, language offices, and Lembaga Adat have already accomplished to preserve the collection so that everyone can learn about the Seloko Tradition Adat in the province of Jambi.